Artificial neural networks : a practical course /: a practical course. ([2016]) - Silva, Ivan Nunes Da; Spatti, Danilo Hernane; Andrade Flauzino, Rogerio; Liboni, Luisa Helena Bartocci; Reis Alves, Silas Franco dos
No abstract available